Different alternative splicing patterns are subject to opposite selection pressure for protein reading frame preservation - Chen, Feng-Chi (BioMed Central|1, 2007)
BACKGROUND: Alternative splicing (AS) has been regarded capable of altering selection pressure on protein subsequences. Particularly, the frequency of reading frame preservation (FRFP), as a measure of selection pressure, has been reported to be higher in alternatively spliced exons (ASEs) than in constitutively spliced exons (CSEs). However, recently it has been reported that different ASE types – simple and complex ASEs – may be subject to opposite selection forces. Therefore, it is necessary to re-evaluate the evolutionary effects of such splicing patterns on frame preservation. RESULTS: Here we show that simple and complex ASEs, respectively, have higher and lower FRFPs than CSEs. Since complex ASEs may alter the ends of their flanking exons, the selection pressure on frame preservation is likely relaxed in this ASE type. Furthermore, conservation of the ASE/CSE splicing pattern increases the FRFPs of simple ASEs but decreases those of complex ASEs. Contrary to the well-recognized concept of strong selection pressure on conserved ASEs for protein reading frame preservation, our results show that conserved complex ASEs are relaxed from such pressure and the frame-disrupting effect caused by the insertion of complex ASEs can be offset by compensatory changes in their flanking exons. CONCLUSION: In this study, we find that simple and complex ASEs undergo opposite selection pressure for protein reading frame preservation, with CSEs in-between. Simple ASEs have much higher FRFPs than complex ones. We further find that the FRFPs of complex ASEs coupled with flanking exons are close to those of simple ASEs, indicating that neighboring exons of an ASE may evolve in a coordinated way to avoid protein dysfunction. Therefore, we suggest that evolutionary analyses of AS should take into consideration the effects of different splicing patterns and the joint effects of multiple AS events.